(untitled) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
This article examines the linguistic features of borrowings in modern English based on technical lexis. The relevance of the study is обусловлена the rapid development of science and technology, which has led to the continuous expansion of English vocabulary through borrowing processes. The aim of the research is to identify the sources, types, and functions of borrowed lexical units in technical discourse. The study employs methods of linguistic analysis, classification, and contextual interpretation. The empirical data include approximately 100 lexical units drawn from technical texts and IT-related discourse. The findings suggest that borrowings play a crucial role in the formation of technical terminology and reflect ongoing processes of globalization and knowledge exchange. It is argued that borrowings contribute to the standardization and internationalization of professional communication